Visual supercompensation following short-term exhaustive exercise - Shaw, Ina; Breukelman, Gerrit; Millard, Lourens; Mathunjwa, Musa Lewis; Shangase, Phindile Zifikile; Muluvhu, Takalani Clearance; Khanmohammadi, Razieh; Brown, Gregory A.; Shaw, Brandon S. (Frontiers in Physiology, 2025)
IntroductionThe human visual system plays a critical role in high-performance tasks, including sports and activities requiring visuomotor performance. While supercompensation is well-documented in aerobic exercise, its effects on visual performance following anaerobic exercise remain unclear. This study investigates whether short-term exhaustive exercise enhances post-exercise visual performance, with a focus on accommodation facility, saccadic eye movements, speed of recognition, peripheral awareness, hand-eye coordination, and visual memory.MethodsA randomised controlled trial was conducted with 128 participants. Participants completed baseline visual assessments followed by a 30-s Wingate Anaerobic Test (n = 68) or no intervention (control group) (n = 60). The same visual tests were repeated immediately post-exercise. Statistical analyses included t-tests, analysis of variance (ANOVA), and effect size calculations (Cohen’s d). Multiple comparison corrections (Bonferroni and Holm) were applied to control for family-wise error rates.ResultsThe experimental group demonstrated significantly greater improvements in visual performance compared to the control group (P < 0.05). Large effect sizes were observed for hand-eye coordination (ES = 1.539), accommodation facility (ES = 1.138), speed of recognition (ES = 1.007), and peripheral awareness (ES = 0.823). Moderate effect sizes were noted for saccadic eye movements for both the left and right charts (ES = 0.679). Post-hoc multiple comparison corrections confirmed significant improvements in speed of recognition, hand-eye coordination, and peripheral awareness (P < 0.000), while accommodation facility showed marginal significance before correction but became non-significant afterward. Visual memory did not significantly differ between groups (P = 0.065).ConclusionThis study highlights that short-term exhaustive exercise can induce transient enhancements in visual performance, particularly in tasks requiring rapid recognition, coordination, and peripheral awareness. Whether similar effects occur in athletes, who likely start from a higher baseline of performance than physically inactive individuals participants, remains unknown. Such visual supercompensation could be valuable for athletes and professionals in fast-paced environments, offering an opportunity to optimise visual-motor function before performance-critical tasks.